Revealing the Oxygen Transport Challenges in Catalyst Layers in Proton Exchange Membrane Fuel Cells and Water Electrolysis - Li, Huiyuan; Yuan, Shu; You, Jiabin; Zhao, Congfan; Cheng, Xiaojing; Luo, Liuxuan; Yan, Xiaohui; Shen, Shuiyun; Zhang, Junliang (Nano-Micro Letters, 2025)
Urgent requirements of the renewable energy boost the development of stable and clean hydrogen, which could effectively displace fossil fuels in mitigating climate changes. The efficient interconversion of hydrogen and electronic is highly based on polymer electrolyte membrane fuel cells (PEMFCs) and water electrolysis (PEMWEs). However, the high cost continues to impede large-scale commercialization of both PEMFC and PEMWE technologies, with the expense primarily attributed to noble catalysts serving as a major bottleneck. The reduction of Pt loading in PEMFCs is essential but limited by the oxygen transport resistance in the cathode catalyst layers (CCLs), while the oxygen transport in anode catalyst layers (ACLs) in PEMWEs also being focused as the Ir/IrOx catalyst reduced. The pore structure and the catalyst–ionomer agglomerates play important roles in the oxygen transport process of both PEMFCs and PEMWEs due to the similarity of membrane electrode assembly (MEA). Herein, the oxygen transport mechanism of PEMFCs in pore structure and ionomer thin films in CCLs is systematically reviewed, while state-of-the-art strategies are presented for enhancing oxygen transport and performance through materials and structural design. The deeply research opens avenues for exploring similar key scientific problems in oxygen transport process of PEMWEs and their further development. Highlights: 1 Mechanisms of the bulk and local oxygen transport in cathode catalyst layers (CCLs) in proton exchange membrane fuel cells (PEMFCs) are presented. 2 State-of-the-art strategies to mitigate the oxygen transport resistance in CCLs in PEMFCs are reviewed, including the novel structure design, carbon supports design, and ionomer design. 3 New directions for oxygen transport development in anode catalyst layers (ACLs) in proton exchange membrane water electrolysis (PEMWEs) are inspired by the PEMFCs.